Tsunami of India’s Second COVID-19 Wave: B.1.617 and Black Fungus - Gautam, Dr. Hemant K. (Asian Journal of Pharmaceutics (AJP), 2022)
The catastrophic second wave of COVID-19 caused over 26 million cases in India making it the epicenter of the global pandemic. The sudden surge in COVID-19 infections is intertwined with various variants including B.1.617. Globally, health authorities have expressed major concerns that key mutations L452R and E484Q located at the receptor-binding domain of the spike protein would have additive effects on SARS-CoV-2 evasion from the vaccine-elicited antibodies. As India struggles with COVID-19 cases spiraling out of control, it is simultaneously caught by escalating cases of “Black Fungus.” Researchers are hurrying to determine the many circulating variants and to know the unknowns about biology and pathology of the mutating SARS-CoV-2 to analyze the threat possessed by them.